Robot technology and applications - Rembold, Ulrich (Manufacturing engineering and materials processing, 1990)
Introduces designers to hardware and software tools necessary for planning, laying out, and building advanced robot-based manufacturing cells surveying the available technology for creating innovative machines suitable to individual needs. Considers assembly system simulation, task-oriented programm